Local demand, urbanization and Amazonian Metropolitan Regions impacts on deforestation of the Brazilian Amazon - Sergio Castelani; Joaquim Guilhoto; Danilo Igliori (European Regional Science Association (ERSA), 2013)
The paper estimates how much of the Amazon deforestation is due to the consumption of goods and services from households who live within the Amazon region itself, comparing it to deforestation driven by consumers who live outside Amazon. As the Brazilian Amazon contains 5 big Metropolitan Regions, and in order to take into account this referred urbanization process, it not only compared the effects of demand vectors from within and outside Brazilian Amazon, but also with the isolated effects from consumption of households who live within the Metropolitan Areas of Brazilian Amazon from the consumption vector of families who live within Amazon, but outside those Metropolitan regions. Using an Inter-regional Input-Output model with socioeconomic data, and crossing this database with information on land use transition from forest areas to agricultural and livestock land use, it finds robust evidence that these local demand vectors play an important role in terms of the deforestation they drive. Results show that even though local population from the Amazon region represents only 13% of total Brazilian population, it drives around 30% of the total deforestation taking place within the region, through its direct and indirect consumption of the output produced in forest areas. The demand vector from families who live within the Amazonian Metropolitan Regions is responsible for more than a half of this 30%, even though only 25% of Amazon population live in these areas. In per capita terms, results also show that the demand vector from one individual living within the Amazon region, but outside the Metropolitan areas, generates 2.2 more deforestation than the consumption vector of one individual living outside Amazon, but within Brazil. For the consumption vector of one individual living within the Amazonian Metropolitan Regions, the deforestation impact is even higher: it is 7.7 times the impact of the demand vector from one individual living outside Brazilian Amazon. The results concerning the economic multipliers and generators, as well as the ones focusing only on the output per sector driven by each regional demand vector also point to this same direction. Therefore, these results bring evidence that support the theoretical expectations from Spatial Economics that local demand vectors and the urbanization process taking place within Brazilian Amazon play an important role in terms of the deforestation it might cause.
Keywords: 330; Amazon; Deforestation; Urbanization; Input-Output